Effect of Low Cost Drip Tape Irrigation System on Yield and Economics of Sweet Corn (Bangladesh Agronomy Journal, 2017)
A study was conducted to determine the effect of low cost drip tape irrigation system on yield and economics of sweet corn in comparison to conventional inline drip irrigation and surface irrigation systems during 2013-14 at Coimbatore, India. The treatment comprises of two drip irrigation systems with three irrigation levels viz., 75, 100 and 125% of pan evaporation (PE) from Class A Pan evaporimeter. Plant height, fresh cob length, girth, number of kernels per cob and single fresh cob weight and yield were higher at 125% PE in conventional in line drip irrigation system and it was statistically at par with drip irrigation at 125% PE in low cost drip tape irrigation system. Water saving was 36, 49 and 62% at 125, 100 and 75% PE, respectively under conventional in line drip irrigation system and drip tape irrigation system as against the surface irrigation. The cost of low cost drip tape system was 68% lower than the conventional inline drip system. The results of the research indicated that based on net income, B:C ratio and GM/TMV ratio, adoption of low cost drip tape irrigation system at 125% PE was found to be best for small and marginal farmers with substantial yield and income compared to conventional inline drip system.Bangladesh Agron. J. 2016 19(2): 71-77